Use in selection of the measurements of feed intake and feeding behaviour parameters in sheep - François D.; Brunel J.C.; Ricard E.; Weisbecker J.L.; Bouix J.; Bourdillon Y.; Bibé B. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Selection of meat sheep concerns currently two groups of traits, on the one hand the reproductive performances and on the other hand the meat traits such as growth and body composition. One way to improve lamb production may be to increase the efficiency of feed transformation by lambs. To avoid behaviour disorders it was necessary to be able to measure individual feed intake of group-reared lambs. In order to do that, the first step of the study was to develop an automatic feeder adapted for young rams. Then, each year, several groups of ram lambs included in individual performance tests had their feed intake measured. The genetic parameters were estimated and heritability coefficients were 0.43 for feed intake, 0.30 for residual daily feed intake estimated by regression of feed intake on growth, weight and body composition. Genetic correlation coefficients of selected traits (growth, weight, fat and conformation) were high with feed intake (0.83, 0.85, 0.31, 0.32) but very low with residual daily feed intake. Consumption of ewe lambs was measured in feedlots and seems to be positively linked with residual feed intake of ram lambs. Some parameters concerning the feeding behaviour have been described and the opportunity of the use of these feeding traits in meat sheep selection is discussed.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)